JAMAL BEY ALBOGACHIEV: PUBLIC AND POLITICAL LIFE IN EMIGRATION - I. L. BABICH; J. SCHNELLE (Кавказология, 2021)
The aim of this article is study social and political activities by ingush Jamal Albogachiev (1894–1949). This is the first study of this person. This article is based on the archives from France and Germany. Albogachiev was educated in Europe, knew European languages, and became a member of the Foreign Delegation of the Mountain Republic (Versailles, 1919). He married a German woman from Berlin. In 1921–1928 he and his family lived in Germany. In France      (1929–1942) Albogaciev lived alone. He collaborated with many public figures: Ali Mardan Topchibashi, brothers Vassan-Girey and Mohammed-Girey Dzhabagiyev. At the same time he worked as a dancer in russian cabarets in Paris. In 1942–1945 Jamal was in Germany, where he became a member of the North Caucasian National Committee. After returning to France, the police investigated the reasons for his stay in Germany. As a result, Jamal was forced to leave for Morocco in 1948, where he died next year. The study of the life of Jamal Albogachiev, his socio-political views and activities showed that his fate was dramatic. Having received an excellent European education and knowledge of European languages, having got to Europe, he could not realize his intellectual potential, couldn’t make a career in Europe. He had the views of the creation of an independent state in the North Caucasus. However, he didn’t become an active member of the most famous and largest emigre movements of the North Caucasus. Despite the fact that he was part of the political North Caucasian elite, he was most often used in secondary or third roles.